Mapping the reception, transmission, and translation of scriptural writings in the EOTC : how and why some "pseudepigraphical" works receive "canonical" status in the Ethiopian Bible - Asale, Bruk Ayele (Journal for semitics, 2013)
The Ethiopian Orthodox Tewahido Church (EOTC) has its own unique history of reception, translation, and transmission of scriptural texts and traditions. This results in a significantly differing collection of scriptural books, where the canon of this church contains both "canonical" and some "pseudepigraphical" works at equally authoritative level. Besides its claim of unique inception, it was the isolated development of the church since the fourth and fifth centuries A.D., when the main translations and transmissions were made, which enabled the church to give similar status to different categories of scriptures. The church never officially debated the limit and extent of the canon, apart from accepting - apparently automatically - some vaguely stated traditions and other suggestions by political figures. This article surveys the major events and turning points in the history of the reception, transmission, translation and collection of the church's scriptures. It aims to offer a systematic overview with regards to how and why the EOTC retains a unique scriptural collection.